Competitive outcome of multiple infections in a behavior‐manipulating virus/wasp interaction. Issue 24 (5th December 2015) - Martinez, Julien; Fleury, Frédéric; Varaldi, Julien
Abstract: Infections by multiple parasites are common in nature and may impact the evolution of host–parasite interactions. We investigated the existence of multiple infections involving the DNA virus LbFV and the Drosophila parasitoid Leptopilina boulardi . This vertically transmitted virus forces infected females to lay their eggs in already parasitized Drosophila larvae (a behavior called superparasitism), thus favoring its spread through horizontal transmission. Previous theoretical work indicated that the evolution of the level of the manipulation strongly depends on whether infected parasitoids can be re‐infected or not. Here, we describe a strain of LbFV that differs from the reference strain by showing a deletion within the locus used for PCR detection. We used this polymorphism to test for the existence of multiple infections in this system. Viral strains did not differ on their vertical or horizontal transmission rates nor on the way they affect the parasitoid's phenotype, including their ability to manipulate behavior. Although already infected parasitoids were much less susceptible to new infection than uninfected ones, frequent coinfection was detected. However, following coinfection, competition between viral strains led to the rapid elimination of one strain or the other after a few generations of vertical transmission. We discuss the implications of these results for the evolution of the behavioral manipulation. Abstract : Multiple infections have a major impact on the evolution of parasite virulence and more generally of parasite extended phenotype. Here we investigated the competitive outcome of multiple infections in a virus manipulating the behaviour of a parasitoid wasp. Our results suggest that competition between viral strains and the potential conflicts of interest emerging in multiply infected hosts should greatly affect the evolution of the behavioural manipulation.